2016
DOI: 10.1111/jgs.14542
|View full text |Cite
|
Sign up to set email alerts
|

Mediation of Cognitive Function Improvements by Strength Gains After Resistance Training in Older Adults with Mild Cognitive Impairment: Outcomes of the Study of Mental and Resistance Training

Abstract: High-intensity PRT results in significant improvements in cognitive function, muscle strength, and aerobic capacity in older adults with MCI. Strength gains, but not aerobic capacity changes, mediate the cognitive benefits of PRT. Future investigations are warranted to determine the physiological mechanisms linking strength gains and cognitive benefits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
81
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 113 publications
(98 citation statements)
references
References 37 publications
11
81
0
Order By: Relevance
“…In these two studies, patients of the experimental group increased their cognition relatively more than the control group after intervention, both for the ADAS-Cog and the MMSE. Other studies showed no significant differences between the conditions with regard to cognition [34,35,45,46,49,51,55,57,58]. Studies that used other assessment tools to measure cognitive impairment showed also positive effects.…”
Section: Skills Training Trialsmentioning
confidence: 94%
See 1 more Smart Citation
“…In these two studies, patients of the experimental group increased their cognition relatively more than the control group after intervention, both for the ADAS-Cog and the MMSE. Other studies showed no significant differences between the conditions with regard to cognition [34,35,45,46,49,51,55,57,58]. Studies that used other assessment tools to measure cognitive impairment showed also positive effects.…”
Section: Skills Training Trialsmentioning
confidence: 94%
“…In particular, Herrera et al [43] found an effect on working memory and recall, where patients improved better than controls after the intervention. Law et al [47] found a positive effect on verbal learning and on the TMT-A, whereby patients in the intervention group showed better functioning than the control, and Mavros et al [49] found that participants of the intervention group scored relatively better on the BVRT and memory domain than control. Ngandu et al [52] found that patients scored better at executive functioning, processing speed, and memory after the intervention compared to the control conditions.…”
Section: Skills Training Trialsmentioning
confidence: 99%
“…The preponderance of research on the effects of exercise on cognition in aging has used aerobic exercise. However, strength training may provide separate or additional benefit to the brain . Even less research has been conducted on the effects of nonexercise movement that reduces sedentary time, which may be an important part of an exercise prescription for maintaining cognition.…”
Section: Discussionmentioning
confidence: 99%
“…https://doi.org/10.1101/19005249 doi: medRxiv preprint Aerobic capacity (VO 2 peak) was determined via indirect calorimetry during a physicianadministered, graded treadmill walking test to volitional fatigue. Methods and data handling have been previously published 16 . Table 1.…”
Section: Assessment Of Peak Aerobic Capacitymentioning
confidence: 99%